1999
DOI: 10.1006/geno.1999.5826
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence-Ready Map of the Human Chromosome 17p Telomere

Abstract: A half-YAC clone derived from human chromosome 17p was mapped at high resolution using cosmid subclone fingerprint analysis. Colinearity of the half-YAC with the telomeric human genomic DNA fragment was ascertained by RecA-assisted restriction endonuclease cleavage mapping. Previously isolated and radiation hybrid-mapped markers TEL17P37, TEL17P49, and TEL17P80 mapped 30-60 kb from the 17p terminus. This sequence-ready map permits high-resolution integration of genetic maps with the DNA sequences directly adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In comparison, in sperm DNA, this sequence is completely devoid of methylation, as has been previously observed (Brock et al 1999). Probe 17tel49, which recognizes a region approximately 35 kb proximal to telomere 17p (Xiang et al 1999), overlapping the region tested for R+S timing, showed similar full methylation in cord blood DNA and early passage fibroblasts, in comparison with a lack of methylation in sperm DNA (Fig. 3b).…”
Section: Methylation Of Subtelomeric Regions In Sperm and Cord Blood Dnasupporting
confidence: 79%
See 1 more Smart Citation
“…In comparison, in sperm DNA, this sequence is completely devoid of methylation, as has been previously observed (Brock et al 1999). Probe 17tel49, which recognizes a region approximately 35 kb proximal to telomere 17p (Xiang et al 1999), overlapping the region tested for R+S timing, showed similar full methylation in cord blood DNA and early passage fibroblasts, in comparison with a lack of methylation in sperm DNA (Fig. 3b).…”
Section: Methylation Of Subtelomeric Regions In Sperm and Cord Blood Dnasupporting
confidence: 79%
“…The distances of these probes from the telomeric repeat region are between 100 and 300 kb, and therefore their hybridization intensity is not affected by age-related telomeric attrition. For four of the cosmids a more precise location relative to the chromosomal end is known: 4q (cosmid cT55), <200 kb, based on interphase FISH (Lese et al 1999); 11p (cosmid 2209a2), maximum 125 kb (http//:www.wistar.upenn.edu/Riethman/telomeres/t11p/t11pseq.html); 16p (cosmid CGG4), ~100 kb (Flint et al 1997); and 17p (cosmid 2111b1), maximum 96 kb (Xiang et al 1999). Cosmid probes for non-telomeric regions are described elsewhere [cJ21 from the CFTR gene locus and CL15 from the muscle glycogen phosphorylase (PYGM) locus (Selig et al 1992) and HG4 from the β-globin locus (Kitsberg et al 1993)].…”
Section: Methodsmentioning
confidence: 99%
“…Genomes labeled with the DLE enzyme showed large differences between mapping patterns for 17p compared with the HG38 reference and further characterization will be needed to accurately classify this arm. Previous 17p subtelomere mapping and sequencing studies showed several discrete large tandem repeat regions within 100 kb of the chromosome end based upon a telomere-containing half-YAC as well as large variations detected by RARE cleavage [30,38]. Both 17p features may be contributing to difficulties characterizing this subtelomere in the population.…”
Section: Discovery Of Novel Subtelomeric Structural Variants Resolutmentioning
confidence: 94%
“…The discovery that telomeres from human chromosomes can be cloned by functional complementation in yeast enabled the molecular characterization of subtelomeric repetitive and chromosome unique DNA (Brown et al 1989;Cross et al 1989;Riethman et al 1989;Bates et al 1990). When yeast artificial chromosome (YAC) vectors with only one functional telomere are ligated to human genomic DNA, clones survive in the yeast host cells if they are stabilized by the presence of a second telomere derived from the human genomic DNA ("half-YACs") (Xiang et al 1999). Characterization of half-YAC libraries produced in this way has resulted in the development of a valuable set of molecular resources for analyzing most, if not all, chromosome ends (National Institutes of Health et al 1996;Rosenberg et al 1997).…”
Section: Introductionmentioning
confidence: 99%